การเพิ่มการถ่ายโอนความร้อนในเครื่องแลกเปลี่ยนความร้อนแบบท่อสองชั้นโดยผลกระทบร่วมของการเคลื่อนที่แบบสลับและการกระตุ้นให้เกิดการปั่นป่วน - ประกิจ ชูหว่าง (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
In this work, we study the method to increase the heat transfer efficiency of double pipe heat exchanger at laminar flow by using the combined effect of oscillatory motion and turbulence promotion. Thermal boundary layer can be decreased by installing periodically spaced orifice baffles. The oscillatory motion is achieved by moving a set of orifice baffles up and down at the top of the tube. The parameters that have effect on heat transfer efficiency are inner hole diameter of buffle plate, space between baffle plates, hot and cold stream flow rates, frequency and vibration amplitude. The relationships between Nusselt number of inner and outer heat transfer surfaces can be shown as functions of oscillatory flow Reynolds number in rang of 0-2,000, hot flow Reynolds number in range of 100-1,000, cold flow Reynolds number in range of 500-2,500, the ratio of inner hole diameter and tube diameter in range of 0.4-0.7 and the ratio of the space between each baffles and tube diameter in range of 1-2.5 are [Equation] and [Equation] , respectively.